Current Clinical Practice Guidelines for the Treatment of Renal Cell Carcinoma: A Systematic Review and Critical Evaluation. (June 2017) - Bamias, Aristotle; Escudier, Bernard; Sternberg, Cora N.; Zagouri, Flora; Dellis, Athanasios; Djavan, Bob; Tzannis, Kimon; Kontovinis, Loukas; Stravodimos, Konstantinos; Papatsoris, Athanasios; Mitropoulos, Dionysios; Deliveliotis, Charalampos; et al.
Abstract: The landscape of local and systemic therapy of renal cell carcinoma (RCC) is rapidly changing. The increase in the incidental finding of small renal tumors has increased the application of nephron‐sparing procedures, while ten novel agents targeting the vascular endothelial growth factor (VEGF) or the mammalian target of rapamycin pathways, or inhibiting the interaction of the programmed death 1 receptor with its ligand, have been approved since 2006 and have dramatically improved the prognosis of metastatic RCC (mRCC). These rapid developments have resulted in continuous changes in the respective Clinical Practice Guidelines/Expert Recommendations. We conducted a systematic review of the existing guidelines in MEDLINE according to the Preferred Reporting Items for Systematic Review and Meta‐Analyses statement, aiming to identify areas of agreement and discrepancy among them and to evaluate the underlying reasons for such discrepancies. Data synthesis identified selection criteria for nonsurgical approaches in renal masses; the role of modern laparoscopic techniques in the context of partial nephrectomy; selection criteria for cytoreductive nephrectomy and metastasectomy in mRCC; systemic therapy of metastatic non‐clear‐cell renal cancers; and optimal sequence of available agents in mRCC relapsed after anti‐VEGF therapy as the major areas of uncertainty. Agreement or uncertainty was not always correlated with the availability of data from phase III randomized controlled trials. Our review suggests that the combination of systematic review and critical evaluation can define practices of wide applicability and areas for future research by identifying areas of agreement and uncertainty among existing guidelines. Implications for Practice: Currently, there is uncertainity on the role of surgery in MRCC and on the choice of available guidelines in relapsed RCC. The best practice is individualization of targeted therapies. Systematic review of guidelines can help to identify unmet medical needs and areas of future research. Abstract : Therapy options for renal cell carcinoma are developing rapidly. This systematic review focuses on the current guidelines for treatment of renal cell carcinoma.